ANALISIS TINDAK TUTUR PADA HASIL TERJEMAHAN TRIBUNNEWS TERHADAP PIDATO MENLU RI RETNO LP MARSUDI DI FORUM PBB 2021 - Pratiwi, Herlina (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2023)
The study of speech acts has become an interesting discussion in the realm of linguistics, therefore, the researcher raised t his title from the previous research which described the quality analysis results of the translations of six mass media for the spe ech of the foreign minister Retno LP Marsudi at the UN meeting on 19 May 2021, one of the mass media that is interesting to study is the transla tion from tibunnews which gets the best quality score of 3.96 from Barnwel's TQA Indicator (Adamsyah, et al. 2021). In this case, the researche r intends to conduct speech act analysis as a sub-study that will discuss locutionary, illocutionary, perlocutionary and performative speech acts. The researcher realizes that the substance or discourse of the speech of the foreign minister Retno LP Marsudi contains various of speech acts because in general it expresses and strongly condemns the actions taken by Israel against Palestine, as we know , there will be lots of sentences that carry a context and produce and command explicit and urgent action. This research is descriptive qualitative with data collection techniques that have been carried out by researchers in a previous study entitled